Colonial Encounters in Southwest Canaan during the Late Bronze Age and the Early Iron Age - Koch, Ido, (Culture and History of the Ancient Near East ;, 2021)
"In Colonial Encounters in Southwest Canaan during the Late Bronze Age and the Early Iron Age Koch offers a detailed analysis of local responses to colonial rule, and to its collapse. The book focuses on colonial encounters between local groups in southwest Canaan (between the modern-day metropolitan areas of Tel Aviv and Gaza) and agents of the Egyptian Empire during the Late Bronze Age (16th-12th centuries BCE). This new perspective presents the multifaceted aspects of Egyptian colonialism, the role of local agency, and the reshaping of local practices and ideas. Following that, the book examines local responses to the collapse of the empire, mechanisms of societal regeneration during the Iron Age I (12th-10th centuries BCE), the remnants of the Egyptian-Canaanite colonial order, and changes in local ideology and religion"--